(untitled) (Jóvenes en la Ciencia, 2024)
Training of healthcare personnel in nosocomial infections focuses on providing the knowledge and skills necessary to prevent the spread of diseases within hospitals and healthcare facilities, thus ensuring the safety of patients and staff. Most nosocomial infections can be prevented; by their nature, they are acquired in the hospital setting; the patient contracts it at least 48 hours after admission to the hospital. The objective of this research work was to identify the level of knowledge of nursing technicians, assistants and graduates at different educational levels at the nursing level. They were previously asked for their informed consent to apply the Survey of knowledge, attitudes and practices on nosocomial infections and standard precautions of hospital staff. Prospective, observational study, which was applied to 38 nurses from the public sector, ISSSTE. It has been shown that 89% of nursing graduates have better preparation, which differs with 74% being nursing technicians and 61% nursing assistants. These results suggest that the level of education that people have is related to the level of knowledge, therefore, it is of utmost importance to provide continuous and updated training to all nursing staff, so that, in this way, they are prepared to any event.